Visual Ranking of Link Structures - Brandes, Ulrik; Cornelsen, Sabine (Journal of Graph Algorithms and Applications, 2003)
Methods for ranking World Wide Web resources according to their position in the link structure of the Web are receiving considerable attention, because they provide the first effective means for search engines to cope with the explosive growth and diversification of the Web. Closely related methods have been used in other disciplines for quite some time. <!—-> We propose a visualization method that supports the simultaneous exploration of a link structure and a ranking of its nodes by showing the result of the ranking algorithm in one dimension and using graph drawing techniques in the remaining one or two dimensions to show the underlying structure. We suggest to use a simple spectral layout algorithm, because it does not add to the complexity of an implementation already used for ranking, but nevertheless produces meaningful layouts. The effectiveness of our visualizations is demonstrated with example applications, in which they provide valuable insight into the link structure and the ranking mechanism alike. We consider them useful for the analysis of query results, maintenance of search engines, and evaluation of Web graph models. <!—->